TYPE STUDY TO IDENTIFY THE PERFORMANCE OF 4000 STUDENTS IN THE EXACT SCIENCES ABOUT FOUR NATURAL’S AREAS IN GUINEA 2012 - Alhassane Toure; Zuo Guoxin (European Scientific Journal, ESJ, 2015)
This is a comparative study of four natural regions of Guinea on basis of the marks obtained in 2012 by students in three subjects of exact sciences (Math, Physics and Chemistry). We have demonstrated method of the type of investigation. This is based on all candidates of the 2012 session of the unique option mathematical science in Guinea, a sample size of 4,000 students; 1,000 students from each of the four regions. We will use inferential statistics to know the mean of the four regions. This type of comparison between the four regions is employed to determine the student’s level of understanding in the exact sciences in Guinea, and to explain general problems relating to education systems through students’ achievements. In addition, we tried to give some explanations about the causes of the results and finally to put evidence to the contribution of national and international organizations in the education system in Guinea and finally to try to explain some remarks about the factors for the effectiveness of the teacher in a general way while using the SPSS software.